2009
DOI: 10.3892/or_00000420
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene, a novel plant-derived antineoplastic agent, increases cisplatin chemosensitivity of lung tumor cells by triggering apoptosis

Abstract: Abstract. ß-Elemene, a new plant-derived anticancer agent with low toxicity, has been reported to be effective in the treatment of leukemia and solid tumors. In the current study, we explored the therapeutic application of ß-elemene in sensitizing lung cancer cells to cisplatin. ß-Elemene considerably enhanced the inhibitory effect of cisplatin on cell proliferation in a time-and dose-dependent manner in the human non-small cell lung cancer (NSCLC) cell lines H460 and A549. Furthermore, this effect of ß-elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 44 publications
5
67
0
1
Order By: Relevance
“…Elemene (1-methyl-1-vinyl-2, 4-diisopropenylcyclohexane) is a novel anticancer agent extracted from the traditional Chinese medicine Rhizoma zedoariae (Li et al, 2009 of China to treat malignant effusions and some solid tumors. This indicates that elemene is a promising agent for the treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Elemene (1-methyl-1-vinyl-2, 4-diisopropenylcyclohexane) is a novel anticancer agent extracted from the traditional Chinese medicine Rhizoma zedoariae (Li et al, 2009 of China to treat malignant effusions and some solid tumors. This indicates that elemene is a promising agent for the treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new approaches, such as novel drugs with mild toxicities or excellent combination regimens, are needed for the treatment of lung cancer. β-Elemene, a type of anticancer drug with a lower cytotoxicity, has been shown to exhibit anticancer effects in many cancer cells, especially lung cancer cells (12,15). In this study, β-elemene inhibited cell proliferation in a dose-dependent manner in A549 cells.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, many studies have indicated that the effect of β-elemene on cell death may be mediated via a mitochondrial cytochrome c release-dependent apoptotic pathway and the reduction of Bcl-2 protein expression (11). Some other reports have shown that β-elemene can reverse chemotherapeutic resistance and enhance the radiosensitivity in lung carcinoma and renal transplant carcinoma cells (12,13). Thus, the combination of VP-16 and β-elemene may be a possible treatment for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that beta-elemene arrests chemoresistant ovarian carcinoma at the G2-M phase and inhibits the proliferation of cells (Li et al, 2005). Other reported that β-elemene could induce apoptosis in prostate cancer cells and lung tumor cells (Li et al, 2009;. β-elemene also inhibits the proliferation of HEp-2 laryngeal cancer cells and induces apoptosis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%